Acceptability of prison-based take-home naloxone programmes among a cohort of incarcerated men with a history of regular injecting drug use - Michael Curtis; Paul Dietze; Campbell Aitken; Amy Kirwan; Stuart A. Kinner; Tony Butler; Mark Stoové (BMC, 2018)
Abstract Background Take-home naloxone (THN) programmes are an evidence-based opioid overdose prevention initiative. Elevated opioid overdose risk following prison release means release from custody provides an ideal opportunity for THN initiatives. However, whether Australian prisoners would utilise such programmes is unknown. We examined the acceptability of THN in a cohort of male prisoners with histories of regular injecting drug use (IDU) in Victoria, Australia. Methods The sample comprised 380 men from the Prison and Transition Health (PATH) Cohort Study; all of whom reported regular IDU in the 6 months prior to incarceration. We asked four questions regarding THN during the pre-release baseline interview, including whether participants would be willing to participate in prison-based THN. We describe responses to these questions along with relationships between before- and during-incarceration factors and willingness to participate in THN training prior to release from prison. Results Most participants (81%) reported willingness to undertake THN training prior to release. Most were willing to resuscitate a friend using THN if they were trained (94%) and to be revived by a trained peer (91%) using THN. More than 10 years since first injection (adjusted odds ratio [AOR] 2.22, 95%CI 1.03-4.77), having witnessed an opioid overdose in the last 5 years (AOR 2.53, 95%CI 1.32-4.82), having ever received alcohol or other drug treatment in prison (AOR 2.41, 95%CI 1.14-5.07) and injecting drugs during the current prison sentence (AOR 4.45, 95%CI 1.73-11.43) were significantly associated with increased odds of willingness to participate in a prison THN programme. Not specifying whether they had injected during their prison sentence (AOR 0.37, 95%CI 0.18-0.77) was associated with decreased odds of willingness to participate in a prison THN training. Conclusion Our findings suggest that male prisoners in Victoria with a history of regular IDU are overwhelmingly willing to participate in THN training prior to release. Factors associated with willingness to participate in prison THN programmes offer insights to help support the implementation and uptake of THN programmes to reduce opioid-overdose deaths in the post-release period.